FACTORS AFFECTING ACCOUNTING INFORMATION SYSTEM PERFORMANCE IN CV. HARI BAIK - Devi, Ni Luh Nyoman Sherina; Manuari, Ida Ayu Ratih; Rengganis, RR. Maria Yulia Dwi; Mirayani, Luh Putri Mas; Putri, Yura Karlinda Wiasa (Graduate Program of Universitas Tarumanagara, 2023)
An accounting information system is effective if the information needed by system users is met and efficient if the system is able to produce information without spending a lot of time in the work process. The goal of this study was to examine the variables that affect the functionality of the accounting information system, including user participation in information system development, individual technical proficiency, support from top management, training and education initiatives, user communication with information system developers, and the location of the information systems department. The test results demonstrate that user involvement in information system development, individual technical proficiency, and top management support have positive effects on the performance of the accounting information system, whereas training and education programs, user communication, information system developers, and the location of the information systems department have no impact on the performance of the accounting information system.